Tripartite Motif-Containing 1 Influences the Prognosis of Cervical Cancer - Ge Zhang; Huan Chen; Yin Tao (Clinical and Experimental Obstetrics & Gynecology)
Background: Deoxyribonucleic acid (DNA) damage repair pathways synergistically promote cervical carcinogenesis. The role of tripartite motif-containing 11 (TRIM11) in DNA repair may influence genomic stability in cervical cancer (CC) and modulate treatment response. This study aimed to analyze the expression and prognostic significance of TRIM11 in CC and across multiple cancer types (pan-cancer analysis). Methods: TRIM11 expression patterns in CC were investigated through integrated bioinformatics analyses using two independent cohorts: transcriptomic data from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) dataset GSE67522. Experimental validation of TRIM11 overexpression in clinical CC specimens was performed through molecular techniques, including quantitative PCR and Western blotting. Survival outcomes were assessed using Kaplan-Meier method, revealing significant correlations between TRIM11 expression levels and both progression-free survival (PFS) and overall survival (OS) rates in TCGA CC cases. Functional pathway associations were elucidated through gene set enrichment analysis (GSEA), identifying TRIM11-related oncogenic mechanisms. Furthermore, a comprehensive pan-cancer evaluation employing TCGA multi-omics data systematically characterized the prognostic relevance of TRIM11 across diverse malignancies. Results: TCGA cohort analysis demonstrated a statistically significant elevation in TRIM11 expression levels in tumor tissues compared to normal controls (p < 0.0001), with consistent validation observed in the GSE67522 cohort (p < 0.0001). Molecular validation experiments confirmed concurrent upregulation of TRIM11 at both the transcriptional (quantitative reverse transcriptase PCR (qRT-PCR), p < 0.05) and proteomic (Western blot, p < 0.05) levels in CC tissues compared to paired adjacent normal samples. Notably, within the context of human papillomavirus (HPV) infection, the GSE67522 dataset highlighted the pivotal role of TRIM11 during malignant transformation, show a significant difference in expression between HPV-positive cancer tissues and matched normal cervical epithelia (p < 0.001). In the TCGA dataset, OS (p = 0.007; HR [high-expression group] = 1.899; 95% confidence interval [CI], 1.189–3.033) and PFS (p = 0.003; HR = 2.035; 95% CI, 1.266–3.273) were significantly longer in patients with CC with lower TRIM11 expression compared to those with higher TRIM11 expression. Subsequently, GSEA in the TCGA dataset showed that TRIM11 is involved in the transforming growth factor beta (TGF-β), calcium, wingless/integrated (WNT), and mitogen-activated protein kinase (MAPK) pathways in CC (p < 0.0001). Pan-cancer analysis showed that TRIM11 expression differed significantly between various tumor tissues and their corresponding normal tissues, and was closely associated with prognosis across several cancer types. Conclusions: This study demonstrated that TRIM11 is overexpressed in CC, and that its overexpression is associated with poor prognosis. Furthermore, its expression was significantly correlated with prognosis across multiple cancers.